A Prediction Model on Personal Perspective in Relation to Self-Efficacy and Work Values of Corrections Officers - Biscocho, Victor R.; Nabe, Nestor C. (Archives of Business Research, 2022)
The purpose of this study was to determine a model from the personal perspective of correctional officers in Davao Prison and Penal Colony Region XI as influenced by self-efficacy and work values. The instrument used in this study was a customized survey questionnaire but modified to contextualize the regional settings applied to 299 Correction Officers using a stratified sampling technique. Data collection was an electronic survey via google forms. Means and Pearson r were used as statistical tools. The results show very high levels of self-efficacy, work values, and personal perspectives. It also showed a significant correlation between self-efficacy, work values, and personal perspectives. In addition, all variables had a significant impact on individual perspectives. Of the variables, self-efficacy has the greatest impact on an individual's perspective.